Consumer attitude towards the use of blockchain technology: Study on the implementation of the "Green Deal" strategy for organic foods - Bogdan Georgescu; Cristian Bogdan Onete; Doru Alexandru Plesea; Sandra Diana Chita; Stefan Sava (Amfiteatru Economic Journal, 2022)
The European Union aims for Member States to achieve climate neutrality by 2050. To this end, the European Commission has launched a set of policy initiatives in The European Green Deal. One of the components is the Farm to Fork strategy, through which the European Union aims to increase, among other things, to 25% of the agricultural areas with organic production, as well as new labeling rules to promote the sustainable consumption of food and organic food. A modern technology that can be used for food traceability is Blockchain technology. The main objective of this paper is to study consumers' perceptions of the possibility of using blockchain technology in the distribution of 'organic' food products. The research was quantitative and followed the specific aspects of the blockchain concept and its use in the distribution and tracking of food and ecological goods, 'organic'. The aim of the research was to develop a predictive model, using the basic regression equation, to obtain a positive perception of the use of blockchain technology for food and environmental goods.
Keywords: L66; L15; C20; 330; agri-food industry; blockchain; consumer trust; organic food